Nutritional supplements use in high-performance athletes is related with lower nutritional inadequacy from food - Sousa, M.; Fernandes, M. J.; Carvalho, P.; Soares, J.; Moreira, P.; Teixeira, V. H. (Journal of Sport and Health Science, 2016)
Background: The use of nutritional supplements (NS) among athletes is widespread. However, little is known about the relationship between nutritional adequacy and NS usage. The aims of this study were to evaluate the NS usage and to compare the nutritional intake from food and prevalence of micronutrient inadequacy (PMI) between NS users and non-users. Methods: Portuguese athletes from 13 sports completed an NS usage questionnaire and a semi-quantitative food-frequency questionnaire assessing information over the previous 12 months. The estimated average requirement cut-point method was used to calculate PMI. General linear models were used to compare nutritional intake and NS usage. Chi-squared tests and logistic regression were performed to study, respectively, relationships and associations between PMI and NS usage. Results: From the 244 athletes (66% males, 13-37 years), 64% reported NS usage. After adjustment, NS users showed a higher intake from food (p < 0.05), for at least 1 gender, for energy, and for 7 of the 17 studied nutrients. The highest PMI were seen for vitamins D and E, calcium, folate, and magnesium. After adjustment, NS users, irrespective of gender, reported lower PMI for calcium (OR?=?0.28, 95%CI: 0.12-0.65), and female users for magnesium (OR?=?0.06, 95%CI: 0.00-0.98). Conclusion: Athletes using NS reported a higher nutritional intake from food, and a lower PMI for several nutrients. Perhaps, those who were taking NS were probably the ones who would least benefit from it.